2009
DOI: 10.3892/or_00000377
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of CTRP3/cartducin contributes to promotion of osteosarcoma cell proliferation

Abstract: Abstract. CTRP3/cartducin, a novel secretory protein, is a member of the C1q and tumor necrosis factor (TNF)-related protein (CTRP) superfamily, and plays important roles in regulating both embryonic cartilage development and postnatal longitudinal bone growth. CTRP3/cartducin is expressed in human osteosarcomas. We hypothesized that CTRP3/cartducin might have a role in osteosarcoma tumor growth and metastasis. Murine osteosarcoma cell lines, NHOS and LM8, were used as a model. RT-PCR analysis showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…CTRP3 is a new type of adipokine that can affect obesity-related cardiovascular diseases (Figure 2), which provides extensive academic research and is considered a promising therapeutic strategy. However, the following areas require further investigation: (Rosen and Spiegelman, 2006) continuous monitor of the change of CTRP3 levels in normal people, sub-clinical stage, prodromal period, clinical stage, and treatment period, and notably, excessive CTRP3 levels possibly promoting vascular calcification; (Scherer, 2006) the influences of CTRP3 on non-diabetes-related cardiomyopathy using a different method to establish study model or diabetes-related cardiomyopathy; (Akoumianakis and Antoniades, 2017) the effects of CTRP3 on pancreatic β cell, adipocyte differentiation or dedifferentiation, and muscle; (Kishore et al, 2004) the potential adverse effects: CTRP3 stimulates osteosarcoma tumor growth (Akiyama et al, 2009), and promotes the transition of prostate cells into cancer cells (Hou et al, 2015). Thus, all research results should be comprehensively evaluated before developing CTRP3 as an effective therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CTRP3 is a new type of adipokine that can affect obesity-related cardiovascular diseases (Figure 2), which provides extensive academic research and is considered a promising therapeutic strategy. However, the following areas require further investigation: (Rosen and Spiegelman, 2006) continuous monitor of the change of CTRP3 levels in normal people, sub-clinical stage, prodromal period, clinical stage, and treatment period, and notably, excessive CTRP3 levels possibly promoting vascular calcification; (Scherer, 2006) the influences of CTRP3 on non-diabetes-related cardiomyopathy using a different method to establish study model or diabetes-related cardiomyopathy; (Akoumianakis and Antoniades, 2017) the effects of CTRP3 on pancreatic β cell, adipocyte differentiation or dedifferentiation, and muscle; (Kishore et al, 2004) the potential adverse effects: CTRP3 stimulates osteosarcoma tumor growth (Akiyama et al, 2009), and promotes the transition of prostate cells into cancer cells (Hou et al, 2015). Thus, all research results should be comprehensively evaluated before developing CTRP3 as an effective therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that many cell lines express CTRP3, such as mouse chondrogenic progenitor (N1511) (Maeda et al, 2006), mouse preadipocytes (3T3-L1a) (Schaffler et al, 2007;Schmid et al, 2012;Li et al, 2015), mouse osteoblast-like noncancer cell line (MC3T3-E1) (Akiyama et al, 2006), mouse osteosarcoma cell line (LM8, NOHS) (Akiyama et al, 2009), TM3 mouse Leydig cells (Otani et al, 2012), and human mesangial cells (HMCs) (Zhang et al, 2016). Even so, CTPR3 is mainly secreted by AT, and considered as an adipokine (Schaffler et al, 2003a(Schaffler et al, , 2007Wong et al, 2008).…”
Section: Ctrp3 Expression In Vitro and In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, C1QTNF1 not only can stimulates aldosterone production in the adrenal glands (Yamauchi et al 2001), but also inhibits collagen-induced platelet aggregation in vascular systems (Lasser et al 2006)). Activating the ERK1/2-signaling pathway, C1QTNF3 is thought to play a role in promoting osteosarcoma cell proliferation (Akiyama et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Overactivation of the hedgehog pathway has been documented in many cancers, 5 including a recent report of GLI1 activation in pancreatic ductal adenocarcinoma cells. 6 Multiple companies are pursuing hedgehog antagonists, including partners Curis Inc. and Genentech Inc., which are running Phase II studies of GDC-0449 for first-line metastatic colorectal cancer, advanced basal cell carcinoma and advanced ovarian cancer.…”
Section: Balancing Actmentioning
confidence: 99%